معوقات تطبيق ادارة الجودة الشاملة بمؤسسات التعليم التقني والفني : دراسة حالة المعهد العالي لتقنيات شؤون المياه العجيلات - عواطف على عبد السلام موسى; المهدي الباروني سالم خبريش (Surman Journal of Science and Technology, 2024)
The Study Aimed to identify the obstacles of the application of total quality Management in Technical and Technical Education institutions, for the year 2018 Case Study of the Higher Institute of Water Technology Al - Ajailat - State of Libya. The problem of the Study was: The non-application of educational institutions for the application of total quality Management in accordance with the established scientific principles, represented in the creation of the environment and the appointment of a competent department of total quality, which is one of the most important constraints, and this was evident at the Higher Institute of Water Technologies Ajailat, which reflected negatively in To overcome some of the obstacles and problems that arise during the evaluation of the educational process in general as quickly as required. The Study tested two hypotheses: there is a statistically significant relationship between the adequate budget for research and development, and the quality of technical and technical Education at the Higher Institute of Water Technology, there is a statistically significant relationship between communication and Community service, and the quality of technical and technical Education at the Higher Institute of Water Technology. The Study used the descriptive method: to describe the phenomenon and its variables, the inductive and deductive approach through observation of phenomena and data collection, using SPSS program. Based on the study problem and assumptions, a soft sample was selected for (60) members of the Study population (98) with 61.2% The Study reached a number of results, including: There is not enough budget for research and development in the Institute, and the Institute is interested in programs that serve the community. As I have reached a number of recommendations, including: The Management of the Institute to pay more attention to programs that serve the community through research, The Management of the Institute to ensure the process of evaluation and development on an ongoing basis in order to make the necessary adjustments and offer alternatives available in its various activities.